Bahasa Indonesia sebagai Magnet Pariwisata : Analisis Keterkaitan Bahasa dengan Pengembangan Industri Pariwisata - Kinaya Aita Yukuri; Dian Pitriyani; Tasya Zennika; Khalfani Tsabit Abror; Mochamad Whilky Rizkyanfi (Bahasa Indonesia Prima, 2024)
Indonesians are essential in various social, cultural, and economic aspects. One interesting aspect that must be considered is Indonesians' contribution to developing Indonesia's tourism industry. In the context of tourism, Indonesia is an attraction that attracts tourists to various tourist destinations. Indonesian also has a vital role in tourism promotion activities. This research uses a descriptive method, and the purpose of this research is to describe, describe, analyze, and identify challenges and opportunities in the development of Indonesian as a means of communicating to improve the tourism industry in Indonesia. To optimize the role of Indonesians in the tourism industry, it is necessary to pay attention to the challenges faced, such as the diversity of languages in Indonesia. Therefore, the recommendation is that policies and programs, such as Indonesian language training for local communities, be supported, and the quality of translation of tourism promotional materials should be improved. By understanding the relationship between the Indonesian language and the development of the tourism industry, a positive synergy can be created between preserving the Indonesian language and culture and developing sustainable and highly competitive tourism.